PENGARUH LAMA WAKTU PINGSAN SAAT PENGANGKUTAN DENGAN SISTEM KERING TERHADAP KELULUSAN HIDUP BENIH IKAN NILA (Oreochromis niloticus) - Hervy Susanto; Ferdinand Hukama Taqwa; Yulisman . (Universitas Sriwijaya, 2014)
ABSTRACT The aims of this research was to know the effect Â of transportation time with closed drying system on unconcious condition for survaival rate of tilapia fry. This research has been done at Aquaculture Laboratory, Aquaculture Study Program, Agriculture Faculty, Sriwijaya University, Indralaya from 21st-24th June 2009. This research was arvanged in Completely Randomized Design (CRD) with four treatments and three replications. The parameters observed in this experiment were conscious time, survival rate, glucose concentrate, oxygen consumption, feed consumption and water quality. The result showed that the time conscious of tilapia fry need about 4.60 until 14.88 minutes, the transportation time was significant on survival rate of tilapia fry. It was because of stress level and glucose concentrate of tilapia fry are increase. The best treatment was 2.5 hours of transportation with survival rate at 99.33%. The closed drying system of transportation can still to do for 5 hours because the survival rate still 81.33%. The reared at 3 days after conscious from tilapia fry transportation showed that not significant result on survival rate and feed consumption. Â Keywords : Tilapia fry, transportation, closed drying system, survival rate